(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Under the current `euro-centric` paradigm ofconservation in India2, the definition of cultural heritage is monument centredlimiting to select buildings which are supposed to be protected like deadmuseum pieces.